Democratic babies? Françoise Dolto, Benjamin Spock and the ideology of post-war parenting advice. Issue 2 (4th May 2019) - Bates, Richard
ABSTRACT: This article looks at the political implications of a subject not always thought of as directly political, but which has an important ideological component: child-rearing advice. The period after 1945 offers an important example of how this topic can interact with developments in political ideology. This article takes the example of France, with substantial comparative reference to the US and Britain. It argues that the mid-twentieth century was characterized by a move from a hygienist and behaviourist approach to child rearing to a more liberal, humanist approach informed by Freudian psychoanalysis. This occurred significantly later in France – in the 1970s – than in Britain or the US, where it is associated with the years immediately after World War II. Through a comparison of two celebrated childcare experts who epitomized the change – Françoise Dolto in France, Benjamin Spock in the US – the paper explores the reasons for this temporal discrepancy. It shows that Anglo-American experts believed that the widespread application of psychoanalytic theory would help produce democratic citizens and ward off the dangers of authoritarian personalities. In France, psychoanalytic approaches became allied with conservative Catholic views of the family and women's roles, with implications for family policy into the twenty-first century.